2020
DOI: 10.3389/fendo.2019.00914
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes of Serum Gonadotropins and Testosterone in Men Revealed by a Large Data Set of Real-World Observations Over Nine Years

Abstract: Environmental rhythmicity is able to affect the hypothalamic-pituitary-gonadal axis in several animals to achieve reproductive advantages. However, conflicting results were obtained when assessing the environmental-dependent rhythmicity on reproductive hormone secretion in humans. This study was designed to evaluate seasonal fluctuations of the main hormones involved in the hypothalamic-pituitary-gonadal axis in men, using a big data approach. An observational, retrospective, big data trial was carried out, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
1
19
0
1
Order By: Relevance
“…Moskovic et al (2012) showed a significant testosterone/estradiol ratio peak in winter in the younger cohort of patients (Moskovic et al, 2012). Santi et al (2020) demonstrated the seasonality of testosterone levels higher in summer, which was correlated to environmental temperatures and daylight duration. LH (luteinising hormone) levels had two peaks of secretion in autumn and spring, while FSH had no seasonal distribution (Santi et al, 2020).…”
Section: F I G U R Ementioning
confidence: 89%
See 4 more Smart Citations
“…Moskovic et al (2012) showed a significant testosterone/estradiol ratio peak in winter in the younger cohort of patients (Moskovic et al, 2012). Santi et al (2020) demonstrated the seasonality of testosterone levels higher in summer, which was correlated to environmental temperatures and daylight duration. LH (luteinising hormone) levels had two peaks of secretion in autumn and spring, while FSH had no seasonal distribution (Santi et al, 2020).…”
Section: F I G U R Ementioning
confidence: 89%
“…The spermatogenesis is critically dependent on the actions of follicle‐stimulating hormone (FSH) and androgen (O'Shaughnessy, 2014). Several studies investigated the seasonal variations in hormones (Moskovic et al., 2012; Santi et al., 2020). Moskovic et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations